2008
DOI: 10.2967/jnumed.107.049718
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG Uptake in Reactive Neck Lymph Nodes of Oral Cancer: Relationship to Lymphoid Follicles

Abstract: PET using 18 F-FDG is acceptable as a preoperative diagnostic tool for head and neck cancer. PET combined with CT provides precise localization of neck lymph nodes. Reactive lymphadenopathy is well known as a principal cause of false-positive findings on PET/CT for nodal staging. We investigated the reactive lymph nodes of oral cancer to elucidate the 18 F-FDG-avid area in these nodes. Methods: Surgically dissected neck lymph nodes of oral cancer were retrospectively reviewed. Of the patients without pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Moreover, it has been showed that the grade of follicular hyperplasia is significantly higher in false-positive lymph nodes than those true-negative lymph nodes. This can be explained by the finding that, besides the inflammatory component above mentioned, dendritic follicular cells consistently express GLUT protein [20,21]. Similar to our case, several studies have reported FDG-PET/CT false-positives in patients with previous history of lymphoma.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, it has been showed that the grade of follicular hyperplasia is significantly higher in false-positive lymph nodes than those true-negative lymph nodes. This can be explained by the finding that, besides the inflammatory component above mentioned, dendritic follicular cells consistently express GLUT protein [20,21]. Similar to our case, several studies have reported FDG-PET/CT false-positives in patients with previous history of lymphoma.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, many prior studies have used either visual assessment or arbitrary pre-set SUV value cutoffs for differentiation/detection of malignant metastasis. [17]. They found that a SUV-max cutoff of 3.5 has 75% sensitivity and 94% specificity for metastasis in enlarged cervical lymph nodes [17].…”
Section: Discussionmentioning
confidence: 97%
“…[17]. They found that a SUV-max cutoff of 3.5 has 75% sensitivity and 94% specificity for metastasis in enlarged cervical lymph nodes [17].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations